2003
DOI: 10.1103/physrevlett.91.187202
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Asymmetric Magnetization Reversal in NanoscaleCo/CoOArrays: Competition between Exchange Bias and Magnetostatic Coupling

Abstract: Magnetization reversal was studied in square arrays of square Co/CoO dots with lateral size varying between 200 and 900 nm. While reference nonpatterned Co/CoO films show the typical shift and increased width of the hysteresis loop due to exchange bias, the patterned samples reveal a pronounced size dependence. In particular, an anomaly appears in the upper branch of the magnetization cycle and becomes stronger as the dot size decreases. This anomaly, which is absent at room temperature in the patterned sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 18 publications
3
50
3
Order By: Relevance
“…More controversial is the effect of reduced lateral dimensions on the magnitude of the EB field, H E . Indeed, some authors reported that H E is enhanced in nanostructures [7][8][9][10], whereas others observed the opposite trend [11][12][13][14][15][16][17][18]. Up to now, this discrepancy has been attributed to the different materials or the nanostructuring techniques employed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More controversial is the effect of reduced lateral dimensions on the magnitude of the EB field, H E . Indeed, some authors reported that H E is enhanced in nanostructures [7][8][9][10], whereas others observed the opposite trend [11][12][13][14][15][16][17][18]. Up to now, this discrepancy has been attributed to the different materials or the nanostructuring techniques employed.…”
mentioning
confidence: 99%
“…Recently, the drastic increase in the areal density of magnetic recording media has motivated the study of EB properties in systems of reduced lateral dimensions [7][8][9][10][11][12][13][14][15][16][17][18][19]. The reduction of the lateral dimensions of an EB system down to length scales comparable to FM or AFM magnetic domain sizes (typically hundreds of nanometers) is also interesting from a fundamental point of view since this results in a confinement and subsequent alteration of the FM and AFM domain structures [10 -13], hence allowing us to probe the role of domains on EB.…”
mentioning
confidence: 99%
“…Coercivity in the front side T-MOKE is not the same as that in the back side, and the amplitudes at the left and right coercivities are asymmetric, indicating that the amount of F spins differ from each other during magnetization rotation between the decreasing and increasing field branches of the T-MOKE loops from the front and back sides of the NiFe/FeMn bilayer. This asymmetric magnetization reversal has been experimentally and theoretically attributed to typical phenomena in a number of exchange-biased F/AF systems [3,[7][8][9][10][11][12][13][14][15][16]. The asymmetric T-MOKE loop for a NiFe/FeMn bilayer seems to originate from the competition between the uniaxial and unidirectional anisotropies [3,13,15].…”
Section: Methodsmentioning
confidence: 99%
“…Various measurement techniques such as VSM, anisotropic magnetoresistance, polarized neutron reflectivity, soft x-ray scattering, and MOKE have revealed the asymmetric form of the magnetization reversal of the exchangebiased F layer [3,[7][8][9][10][11][12][13][14][15][16]. The magnetization reversal takes place via magnetization rotation or via nucleation and domain wall propagation along the same or different sides of an applied field during the decreasing (from positive to negative saturation) and increasing (from negative to positive saturation) field branches of the M-H loop.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the forward and backward branches of the magnetization reversal are performed in different modes, such as the separated ways of magnetic moment rotation [5][6][7][8], the distinct nucleation sites and abilities of the inverse domain [9][10][11][12][13][14][15][16][17][18], and the unsymmetrical training and recovering effect of the pinning of the UCAS [3,[19][20][21][22]. Most AMRBs, except for the loop shift, have their particular features in the specific EB systems, which strongly depends on the structure [1,4,23,24] and measuring methods [4,[9][10][11][25][26][27][28]. The appearances of the AMRBs are so complex that the comprehension on the origin and the classification of the AMRBs is still in debate.…”
mentioning
confidence: 99%